Performance of pedestrian bamboo bridge fabricated by the students - Sonar, Ishwar P.; Joshi, Purva A.; Rupnavar, Pallavi J.; Bulbule, Pooja S. (Journal of Structural Engineering, 2024)
Every year Alumni College of Engineering Pune (COEP) organises students techno-craft competition for all undergraduate students for their innovative small projects. Considering strength properties of bamboo, a group of three girl students from second year civil engineering fabricated a proto-type of pedestrian bamboo bridge with reinforced concrete slab deck panel of width 1.5m and span 4.5m using the limited funds available in the competition held in year 2014-15. The model was tested for the live load and it was observed that bridge sustained the maximum load of crowd without failure of any member of the bridge. In short term loading case, maximum deflection shown by the bridge was within permissible limit. The project have demonstrated importance of bamboo as eco-friendly, economical structural material. Students received field experience on fabrication of bolted connections due to this project. Bamboo bridge of different configuration can be tried and there is lot of scope in research works in development of stiffness of bamboo bridges and techniques in improvement of durability of bridges.